STUDY ON EXPANSIVE SOIL CHARACTERISTICS WITH IDENTIFICATION USING METHYLENBLUE TEST AND X-RAY DIFFRACTION TEST AND IMPROVEMENT WITH CEMENT AND LIME - Fadhl 'abbas, Muhammad
Expansive soils are a problem that exists throughout the world. Expansive soils often cause severe damage to infrastructure due to changes in the volume that is shrinking and taking up its water content. The problems arise when the pressure of the pressure exceeds the load on the foundation until the foundation is lifted. Structures that are often damaged by expansive soils are foundation, retaining walls, road pavements, airports, and riverbeds. Expansive soils have various clay minerals which influence soil properties and behaviors, as well as swell potential. In this study, testing on expansive soil suspect were conducted, i.e. X-Ray Diffraction Test and Specific Gravity Test. The results show that the expansive soil suspect contains high kaolinite clay mineral content. Further testing on soil expansivity has not been conducted, so that soil expansivity cannot be determined. In this research, literature study also conducted on expansive soil identification methods. Because clay minerals have similar chemical composition, then clay mineral identification that is exist in expansive soils hard to determine. Expansive soil stabilizations with cement and lime were studied in this research. Free swell and swell pressure dropped more than 50% from the initial value after adding cement or lime by 6%. MBV also decreased after cement or lime were added, which indicates the soil expansivity. Dry Density Maximum of expansive soils also decreased after cement and lime added to the soil. At the same time, Optimum Moisture Content were observed to be increased after cement and lime were added. The same things also observed on cement lime mix. In terms of soil strength, based on UCS and CBR value, cement or lime increased soil strength. However, after certain contents, lime addition would decrease soil strength, which is in this research, the values are between 9-12 percent. The same things also observed on cement lime mix.